Optimization of the task of forming a management system of hierarchical multilevel complex organizational systems - Zuev, A S; Smolentseva, T E; Isaev, R A (Journal of physics. Conference series, 2021)
A hierarchical configuration procedure in the process of analyzing the functioning of organizational structures using algorithms for solving problems using discrete programming methods is considered in detail in this paper. On the basis of the research, the authors propose a methodology for the combined application of an initial approximation algorithm with certain properties and an algorithm for a recursive procedure for a directed search for the optimal hierarchy, which, in the future, solving the traveling salesman problem in a minimum time much more efficient than using the methods of dynamic programming of branches and boundaries.